Invisible Engines : How Software Platforms Drive Innovation and Transform Industries - Evans, David S. (David Sparks), 1954- (Book collections on Project MUSE., 2006)
'Invisible Engines' examines the business dynamics & strategies used by firms that recognize the transformative power unleashed by the business & technology revolution - a revolution that will change both new & old industries.